Long term mortality of deep sternal wound infection after coronary artery bypass surgery - Moraes,Aline Alexandra Iannoni de (2012)
BACKGROUND: Deep sternal wound infection and mediastinitis determine high in-hospital mortality. International studies show that these patients are also at increased cardiovascular mortality risk in long-term follow-up. However, data are scarce and there is no national data. OBJECTIVES: The aim of this study is to evaluate the mortality and incidence of cardiovascular events in long-term follow-up of patients suffering from deep sternal wound infection and mediastinitis. METHODS: Case-control study, matched by propensity score in a 1:1 proportion, in patients submitted to coronary artery bypass grafting between 2005 and 2008 at the Institute Dante Pazzanese of Cardiology (São Paulo, SP, Brazil). The primary outcome was death. As a secondary outcome, we analyzed the composite event of myocardial infarction, new revascularization, stroke or death. RESULTS: Of 1975 patients, 114 developed one of the infections. During the mean follow up of 3.6 years, deep sternal wound infection and mediastinitis increased the risk of death by 8.26 (95% CI 1.88-36.29, P = 0.005) and the incidence of combined end point by 2.61 (95% CI 1.2-5.69, P = 0.015). The Kaplan-Meier curves for both outcomes demonstrated that the greatest risk occurs in the first six months, followed by a period of stabilization and further increase in the incidence of events after 4 years of hospital discharge. The similarity between the curves of primary and secondary outcomes may be consequent to the predominance of death on the combined cardiovascular events. CONCLUSION: The presence of deep sternal wound infection or mediastinitis increased mortality in long-term follow-up in this sample of the Brazilian population according to the same pattern displayed by the developed countries.